2018
DOI: 10.1590/s1984-296120180033
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies anti-trypanosomatides in domestic cats in Paraná: who is at highest risk of infection?

Abstract: The aim of this study were to detect antibodies anti-Leishmania spp. and anti-Trypanosoma cruzi in two different populations of domestic cats (Felis catus domesticus) from North Paraná referred for surgical castration and to determine which characteristics of the animals studied may be associated with seropositivity. Serum samples from 679 cats were analyzed using enzyme-linked immunosorbent assay (ELISA) and indirect immunofluorescence antibody test (IFAT) in series. Associations between age, sex, race, year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…The FeL seropositivity here was higher than that observed in Recife and Teresina, where 3.9% and 4% of the cats were found be seropositive for FeL using ELISA (SILVA et al, 2014;MENDONÇA et al, 2017). Sero-epidemiological investigations in other regions of the country found frequencies varying from 0.5% to 54%, using IFAT and the same cut-off value adopted here (1:40) (VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;COURA et al, 2018;MATOS et al, 2018). In canine leishmaniasis, high serological titers (four times the established cut-off value) with clinical signs compatible with leishmaniasis are diagnostic for the disease (SOLANO-GALLEGO et al, 2011).…”
Section: Introductionmentioning
confidence: 39%
See 1 more Smart Citation
“…The FeL seropositivity here was higher than that observed in Recife and Teresina, where 3.9% and 4% of the cats were found be seropositive for FeL using ELISA (SILVA et al, 2014;MENDONÇA et al, 2017). Sero-epidemiological investigations in other regions of the country found frequencies varying from 0.5% to 54%, using IFAT and the same cut-off value adopted here (1:40) (VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;COURA et al, 2018;MATOS et al, 2018). In canine leishmaniasis, high serological titers (four times the established cut-off value) with clinical signs compatible with leishmaniasis are diagnostic for the disease (SOLANO-GALLEGO et al, 2011).…”
Section: Introductionmentioning
confidence: 39%
“…In Brazil, studies on FeL using serological, parasitological, and molecular methods revealed that infection frequencies varied from 0% to 54% (BRESCIANI et al, 2010;VIDES et al, 2011;CARDIA et al, 2013;BRAGA et al, 2014;SILVA et al, 2014;SOUSA et al, 2014;OLIVEIRA et al, 2015;GODOI et al, 2016;MENDONÇA et al, 2017;COURA et al, 2018;MATOS et al, 2018). Only a small fraction of these studies was performed in the Northeast region that was home to 82.5% of all reported cases of human leishmaniasis in Brazil between 1980 and 2005, making this region an area of epidemiological relevance for this disease in Brazil (MAIA-ELKHOURY et al, 2008;SILVA et al, 2014;MENDONÇA et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This methodology demonstrates greater sensitivity in clinically affected felines (Persichetti et al 2017). In several studies around the country a higher seroprevalence of FeL was found by ELISA when compared to IFAT (Figueiredo et al 2009;Coelho et al 2011b;Vides et al 2011;Sobrinho et al 2012;Matos et al 2018). Although FeL seroprevalence in Brazil is relatively low, some studies have shown high positive results in endemic areas of the country, as seen in Londrina, Paraná state, Brazil, recording a seroprevalence of 43.4% (295/679) (Matos et al 2018) and in Ilha Solteira, São Paulo state, Brazil showing a seroprevalence of 31.91% (30/94) (Leonel et al 2020).…”
Section: Diagnostic Methods For Felmentioning
confidence: 99%
“…longipalpis(SALES et al, 2015;GONZÁLES et al, 2017). Informações sobre os hábitos alimentares desses vetores são importantes para definir os potenciais reservatórios de L. infantum(GUIMARÃES-E-SILVA et al, 2017) DE MATOS et al, 2018;IATTA et al, 2019;CAMPRIGHER et al, 2019),. alguns mostram que machos são mais acometidos(SOBRINHO et al, 2012;MONTOYA et al, 2018); e outros fêmeas(COSTA et al, 2010) Oliveira et al (2015).…”
unclassified